Chronic anemia due to gastrointestinal bleeding: when do gastroenterologists transfuse?. Issue 7 (1st November 2017) - Grooteman, KV; van Geenen, EJM; Kievit, W; Drenth, JPH
Abstract : Background: The hypothesis is that decision‐making for transfusion varies considerably among gastroenterologists. The aim is to identify preferences and predictors of transfusion decision‐making in chronic anemia. Study design and methods: Between February and April of 2015, a computerized adaptive choice‐based conjoint survey was administered to gastroenterologists in the Netherlands. The survey included seven patient attributes: hemoglobin levels, hemoglobin stability, age, iron indices, the presence of anemia‐related symptoms, cardiovascular comorbidities, and the number of transfusions in the past half year. Predictors of transfusion preferences were assessed by multivariable regression. Results: 113 gastroenterologists completed the survey (response rate = 29%; mean age = 47 years; 24% women). Absolute hemoglobin level was the most important incentive of transfusion, accounting for 42% of decision‐making, followed by age (15%), hemoglobin stability (12%), anemia‐related symptoms (10%), and cardiovascular comorbidities (10%). A hemoglobin level >9.6 g/dL is an inflection point, where gastroenterologists would not prescribe transfusions. Age of the patient is more important in the decision‐making process to younger gastroenterologists (OR −2.9, 95% CI −5.3 to −0.5). Conclusion: Absolute hemoglobin level is the most important factor to transfusion decision‐making. This is contradictory to transfusion guidelines for chronic anemia which address the importance of symptoms.